Case Report: Brain tumor’s pitfalls: two cases of high-grade brain tumors mimicking autoimmune encephalitis with positive onconeuronal antibodies - Consoli, Stefano; Dono, Fedele; Evangelista, Giacomo; Corniello, Clarissa; Onofrj, Marco; Thomas, Astrid; Sensi, Stefano L. (Frontiers in Oncology, 2023)
Background: Glioblastoma (GBM) is the most common primary brain tumor in adulthood. Initial diagnosis is generally based on clinical and MRI findings, which may be misinterpreted as other neurological pictures, including autoimmune encephalitis (AE). AE is a heterogeneous group of neuroinflammatory diseases due to the presence of auto-antibodies targeting antigens on neuronal synaptic or cell surfaces. In the present report, we describe two peculiar cases of GBM initially misdiagnosed as AE, focusing on the diagnostic pitfalls and the treatment strategies.We report the case of two patients with high-grade brain tumors, initially misdiagnosed and treated for AE. Clinical, laboratory, and neuroradiological data are discussed in terms of differential diagnosis between AE and GBM.The presence of atypical brain MRI findings and the unresponsiveness to immunosuppressive treatment are major red flags in the differential diagnosis between AE and GBM. In these cases, a brain biopsy is necessary to confirm the diagnosis.Conclusions: Atypical brain tumor presentation causes a diagnostic and therapeutic delay. A positive onconeural autoantibodies result should always be interpreted cautiously, considering the possibility of a false-positive test. A brain biopsy is mandatory for a definite diagnosis.